Development and evaluation of a novel subunit vaccine for Mycoplasma gallisepticum - Moura L.* (2012)
Adhesion proteins from Mycoplasma gallisepticum (MG) encoded by cytadhesion genes mgc1 and mgc2 were cloned into plasmid vectors and transformed into E. coli. Seventeen groups of specific-pathogen free (SPF), birds at four weeks of age were used to inoculate these two proteins (MGC1 and MGC2) mixed into an oil emulsion creating a novel MG vaccine. Six different protein concentrations (50, 100, 200, 400, 800, and 1000μg/bird) were tested with two equal concentration doses at four and seven weeks of age. In addition, many control groups were needed such as bacterin, membrane, no vaccine or challenge, oil emulsion alone, and no vaccine but challenged. Three weeks following the second vaccination, 50% of the birds in each treatment group were challenged with MG strain S6. The remaining birds were left as contacts to verify protection against horizontal transmission. All birds were bled before vaccinations, challenge and euthanasia. Birds were negative for MG at the first vaccination, as shown by serum plate agglutination test. At necropsy, tissue samples (trachea, lungs, and air sacs) were collected for histopathological examination. Swabs from trachea were used for PCR analysis. ELISA results showed a strong immune response to both protein preparations and almost the same response level for different doses tested, proving the immunogenic features of MGC1 and MGC2. However, humoral responses failed to prevent MG infection and disease when challenged as demonstrated by PCR and histopathology. MGC1 contact birds showed some degree of infection by PCR analysis. In addition, histopathological and ELISA results suggest that contact birds did not have enough time to develop lesions and to mount an immune response.